Physiological profiles and performance predictors of a women's NCAA rowing team - Perkins, C. D.; Pivarnik, J. M. (The Journal of Strength and Conditioning Research, 2003)
We described the physiological profiles of rowers (N = 16; age = 20.1 ± 1.4 years, weight = 78.6 ± 9.5 kg, height = 177.5 ± 3.1 cm) of the top 2 varsity boats on an NCAA women's crew and determined whether physiological measures predict boat assignment as determined by the head coach. Eight participants were members of the top varsity boat (1V) and 8 competed at a lower level (2V). Expired gases were collected while subjects completed the U.S. National Team O2max (3-minute stages) and 2 kilometer (2K) time trial rowing ergometer protocols. Heart rates (HR) and blood lactates were measured before, during, and after each test. The O2max and blood lactate at stage 2 of the O2max test were used to predict boat assignment. Average (±SD) O2max was 3.86 ± 0.40 L·min-1. The 2K times averaged 453.0 ± 10.5 seconds. Subjects used approximately 96% of O2max and 98% of HRmax during the 2K time trials. Neither O2max nor submaximal lactate were related to boat assignment. The O2 values during the 2K trial indicated that rowing economy differed among athletes. Results of physiological measures should help the coach individualize workouts of top performers.